CHANGE IN CHORIOCAPILLARIS FLOW DEFICITS WITHIN TEARS OF THE RETINAL PIGMENT EPITHELIUM IMAGED WITH SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 11 (November 2022) - Iyer, Prashanth G.; Chu, Zhongdi; Shen, Mengxi; Shi, Yingying; Trivizki, Omer; Zhang, Qinqin; Feuer, William; Wang, Ruikang K.; Gregori, Giovanni; Rosenfeld, Philip J.
Abstract : Swept-source optical coherence tomography angiography imaging of three patients before and after the onset of retinal pigment epithelium tears showed that choriocapillaris flow deficit measurements remained stable within the bed of the retinal pigment epithelium tears for at least 16 months after their onset. Abstract : Purpose: Choriocapillaris (CC) flow deficits (FDs) were measured in the areas exposed by tears of the retinal pigment epithelium (RPE) before and after their onset to determine their change over time. Methods: Patients enrolled in a prospective, swept-source optical coherence tomography angiography (SS-OCTA) study were retrospectively reviewed for RPE tears, and scans were evaluated before and after RPE tear formation. Choriocapillaris flow deficits were measured within the bed of the tear and within a symmetric control region. Results: Three patients with RPE tears were imaged before tear formation and for at least 16 months afterward. When the baseline and first posttear visit were compared, CC FDs decreased by 1.0% in the tear region and 1.7% in the control region ( P = 0.84). When the 16-month follow-up visits were compared with the first post-RPE tear visits, CC FDs decreased by 1.9% in tear regions and increased by 1.3% in control regions ( P = 0.37). Conclusion: No significant changes in CC FDs were observed before and after RPE tear formation and for 16 months afterward, suggesting that CC FDs can be reliably detected in the presence of an intact RPE and the absence of the RPE did not affect CC perfusion for at least 16 months.